Implementasi Manajemen SDM Berbasis Kompetensi untuk Meningkatkan Profesionalisme Pegawai: Studi Kasus Perusahaan Devos Jok - Vinky Putri Amelia; Umi Kulsum Zaini; Moh. Rizqi Abadi; Nu’man Hakki Barruka (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to examine the implementation of competency-based human resource management (HR) in improving employee professionalism at Devos Jok, an SME engaged in the automotive interior manufacturing sector. A descriptive qualitative approach is used to explore in depth the HR practices carried out, the challenges faced, and the impact on employee work quality. The results of the study indicate that the transformation of the HR system from an administrative pattern to a competency-based one has made a significant contribution to improving individual and organizational performance. The strategies implemented include competency-based recruitment, ongoing training, flexible payroll systems, and adaptation to digital platforms. However, challenges remain, especially in overcoming resistance to change and limited training resources. This study provides theoretical and practical contributions to the development of a competency-based SME HR system in the context of today's creative and digital industries.